Production and Characterization of Extremophilic Proteinases From a New Enzyme Source, Barrientosiimonas sp. V9 - Flores-Santos J.C. (2020)
Microbial proteases are widely used as commercial enzymes, which have an active role in several industrial processes. The aim of this study was to investigate the production and properties of extracellular proteases from Barrientosiimonas sp. strain V9. The cultivation conditions for protease production were studied using different carbon and nitrogen sources. Maximum protease production was obtained in medium containing 25 g L?1 sucrose, 7 g L?1 KNO3, and initial pH 7.0 at 35 °C and 150 rpm during 72 h. Under these conditions, maximum proteolytic activity reached 1200 U mL?1. The enzyme extract showed optimum activity at 60 °C, pH 9.0, and was stable from 30 to 50 °C within a pH range from 4.0 to 10.0 and NaCl concentration up to 2.5 M. The enzyme was stable in the presence of EDTA, urea, Triton X-100 and laundry detergent (sodium lauryl sulfate as main component). The addition of 1% sodium dodecyl sulfate, Tween-80, or Tween-20 increased the activity by 183% and 119% respectively, while 2-mercaptoethanol reduced the activity to 71%. Casein zymogram analysis revealed three hydrolysis zones suggesting that Barrientosiimonas sp. V9 expresses proteases with molecular weights about 60, 45, and 35 kDa, which were inhibited in the presence of phenylmethylsulfonyl fluoride. Barrientosiimonas sp. V9 produces halotolerant serine proteases with great biotechnological potential. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.